2000
DOI: 10.1007/s11661-000-0076-4
|View full text |Cite
|
Sign up to set email alerts
|

On the infiltration behavior of Al, Al-Li, and Mg meltas through SiC p bed

Abstract: Aluminum, , and Mg matrix composites with uniform distributions of SiC p reinforcement have been prepared by the vacuum infiltration technique. The infiltration kinetics have been found to increase in the order of Al, Al-Li, and Mg. The Al-Li alloy and Mg as matrix materials have shown improved wettability with SiC p in comparison to Al, leading to enhanced infiltration kinetics and reduced reinforcement degradation in the former cases. The infiltration kinetics are insensitive to preheat temperature beyond a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…6(a) shows the solidification microstructure of AZ91 magnesium alloy reinforced by SQCM under normal casting condition. As reinforced phase, quasicrystal phase is distributed in the ␣-Mg matrix or around ␤-Mg 17 Al 12 phase, with smaller particle size than that fabricated by low alloying or melt infiltration [14][15][16]. Due to low surface energy on the quasicrystal particle surface [17] as well as similarity between the quasicrystal phase and the matrix, excellent wetting of the quasicrystal phase with the matrix can be obtained.…”
Section: Mechanism Of Strengthening and Toughening Of Sqcm Master Allmentioning
confidence: 99%
“…6(a) shows the solidification microstructure of AZ91 magnesium alloy reinforced by SQCM under normal casting condition. As reinforced phase, quasicrystal phase is distributed in the ␣-Mg matrix or around ␤-Mg 17 Al 12 phase, with smaller particle size than that fabricated by low alloying or melt infiltration [14][15][16]. Due to low surface energy on the quasicrystal particle surface [17] as well as similarity between the quasicrystal phase and the matrix, excellent wetting of the quasicrystal phase with the matrix can be obtained.…”
Section: Mechanism Of Strengthening and Toughening Of Sqcm Master Allmentioning
confidence: 99%
“…Figure 6 shows an example of the results of Vickers microhardness test for the specimens with a strongly bound SiC particle/matrix interface and a weakly bound interface. Murty et al 15) have reported that the stronger the reinforcement particles bond to alloy matrix, the higher the Vickers hardness becomes. However, in the present work, the hardness values for the specimen with a strongly bound interface are almost constant and a little higher than the intrinsic hardness of SiC (HV = 2800), 16) which may be caused by ''spring-back'' of alloy matrix on unloading.…”
Section: Evaluation Of Bonding Strength Of the Interface Bymentioning
confidence: 99%
“…Dhindaw et al 6) have reported that the stronger the reinforcement particles bond to alloy matrix, the higher the Vickers hardness becomes. Figure 11 shows an example of the results of microvickers hardness test carried out on the Al 2 O 3 particle/AlCu composite with strongly bound particle/matrix interface and weakly bound interface.…”
Section: Effect Of Superheat Of Alloy Melt On Infiltration Ratementioning
confidence: 99%